Post Covid-19 Authentic Assessment of Grade VI Students - Hariyanto, Agus; Wulandari, Murfiah Dewi (Nur Science Institute, 2022)
Background: The transition from online to face-to-face learning after the COVID-19 pandemic has presented new challenges, particularly in implementing authentic assessment. This research aims to explore how authentic assessment is conducted post-pandemic, the obstacles teachers encounter, and strategies employed to overcome these challenges. Method: This study utilized a qualitative descriptive method. Data were collected through interviews and documentation analysis from sixth-grade teachers and the principal of SD Negeri 2 Jatisawit, Jatiyoso District. Data validity was ensured using source and methodological triangulation, while analysis was performed using Miles and Huberman’s interactive model. Result: Authentic assessment implementation post-pandemic involved clearly defined standards aligned with lesson plans (RPP), diversified assessment tasks (portfolio, projects, performance, written assessments), and systematically developed criteria and rubrics. Obstacles identified included disparities in student abilities, limited assessment time, inadequate infrastructure, and limited technological skills among teachers and students. Teachers addressed these by implementing differentiated instruction, utilizing median standards, providing enrichment and remediation, enhancing assignment creativity, and improving their technological competence. Implication: The findings suggest practical approaches for teachers and school administrators to effectively implement authentic assessment, addressing the diverse needs of students and limitations of available resources in post-pandemic situations. Novelty: This study provides specific strategies for differentiated authentic assessment, uniquely adapted to address challenges resulting from the COVID-19 pandemic in an elementary education setting